New conductometric method for measure sap velocity in the xylem of isolated branches - Bara Temes, S. (Forest Systems, 1992)
By using a portable conductimeter detector equipped with a two needle probe, it is possible to measure the sap velocity in the xylem of isolated branches by submerging the cut end in a solution of potassin chloride, of adequate concentration. Saline solution contact with the probe causes a increase in conductivity. The velocity is determined from three measurements at three predetermined distances from the probe and by adjusting velocity value readings according a second degree polynomial. Extrapolation of velocity to zero distance then gives the independent value, corresponding to the result. This is necessary since the apparent velocity depends on the distance of the probe from the cut point, which is in turn correlated to salt retention in branch transport. Velocities obtained by our method exceed those quoted in the bibliography for trees, by the heat impulse method, with the exception of conifers for which there is correlation